Formulation of Liquid Hand Washing Soap Preparation with Guava Leaf Extract (Psidium guajava L) - Resta Mayang Sari; Hasty Hamzah; Sri Yolandari (Journal of Health Science and Pharmacy, 2026)
Background: Medicinal plants have long been utilized as natural sources of bioactive compounds for healthcare products. Guava leaves (Psidium guajava L.), which are widely found in tropical regions, contain various phytochemical constituents, including psiditanins, eugenol, resins, essential oils, fatty oils, mineral salts, and flavonoids. Flavonoids, particularly quercetin, possess antioxidant and antibacterial properties that may help inhibit microbial growth and reduce oxidative stress, making guava leaves a potential ingredient for liquid hand soap formulations. Objective: This study aimed to formulate liquid hand soap preparations containing guava leaf extract (Psidium guajava L.) and evaluate their physical characteristics and quality. Methods: An experimental study was conducted using guava leaf extract at concentrations of 1%, 2%, and 3% in liquid hand soap formulations. The prepared formulations were evaluated through organoleptic testing, homogeneity testing, pH measurement, and foam stability testing to assess their physical quality and stability. Results: The organoleptic evaluation showed that all formulations produced a liquid preparation with a brownish-green color and a characteristic guava leaf odor. Homogeneity testing indicated that all formulations were homogeneous and free from visible granules. The pH test revealed an average pH value of 8 for all formulations, which falls within the acceptable range for liquid soap preparations. Foam stability testing demonstrated that Formula I exhibited the highest foam stability (95.45%), followed by Formula II (88.57%) and Formula III (69.56%). Overall, all formulations met the required standards for foam stability. Conclusion: Guava leaf extract (Psidium guajava L.) can be successfully formulated into liquid hand soap preparations with acceptable physical characteristics, homogeneity, pH, and foam stability. Among the tested formulations, Formula I showed the best foam stability performance. Keywords: Guava Leaf Extract; Psidium guajava L.; Liquid Hand Soap; Formulation; Foam Stability; Antibacterial Activity